PENERAPAN TEORI PEMBELAJARAN BEHAVIORISTIK UNTUK MENGATASI MOTIVASI RENDAH DAN PERILAKU TIDAK SADAR SISWA DI SEKOLAH-SEKOLAH INDONESIA - Althaf Reifa Ardhana; M. Mamduh Winangun (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This article discusses behavioristic learning theory that can be implemented to address two common problems in Indonesian schools, namely low student motivation to participate in the learning process and undisciplined behavior in the classroom. Based on educational reports and several studies, many students appear less enthusiastic in learning, rarely actively engage during lessons, and often violate rules, such as arriving late, leaving the classroom without permission, or failing to follow regulations. In behavioristic theory, the learning process is defined as a directly observable change in behavior. This change occurs due to the relationship between stimulus and response, and through consistent reinforcement and punishment. This article also demonstrates several ways teachers can implement the theory, such as providing clear rewards and consequences, shaping good behavior through repeated practice, and using techniques like token economy (point or reward systems) and shaping (gradually forming behavior). If implemented properly, this approach can increase students' extrinsic motivation, encourage them to be more active in class, and improve discipline. Over time, these positive behaviors can develop into habits.